AB InBev and SABMiller: building the first truly global beer company - Bourban, Hippolyte (2017)
This case study describes the attempt from AB InBev to acquire SABMiller all along the way, from the initial approaches in 2015 until July 2016. It adresses the issues caused by attempting to combine the two largest brewers in the world and the unexpected vote on Brexit which forced AB InBev to revise its initial offer.